Complexity of the well living.: Weighting based on the notions of quality of life, health, well-being, happiness and sustainability - Alves, Lidiane Aparecida (Geografares, 2020)
The purpose of this article is to analyze the notions of quality of life, well-being, happiness, health and sustainability to identify the associations between them. Therefore, they are discussed in a theoretical-conceptual way, as well as seeks to contextualize them empirically, in an objective and subjective way, in Uberlândia-MG. To achieve the goal, a bibliographic review is combined with analysis of primary and secondary datas. It is pointed out that despite the intrinsic relations and some overlaps between such notions, they differ. Sustainability presupposes a collective understanding, and, like health, it is fundamental in the objective dimension, but not only on that, conserning its strong interrelation with the quality of life. For happiness and quality of life, the dimension stands out, which presupposes understanding from the individual scale